Undermining mobilization? The effect of job flexibility and job instability on the willingness to strike. (February 2017) - Jansen, Giedo; Akkerman, Agnes; Vandaele, Kurt
This article addresses the question of whether, and to what extent job flexibility is detrimental to mobilization with regard to the willingness to take part in industrial action. The authors examine the influence of job flexibility ('standard' versus 'non-standard' work) and job instability (changes from one job to another) on employees' willingness to strike. Based on Dutch survey data it is shown that only minor differences exist between 'standard' and 'non-standard' employees in their willingness to participate in a strike. While this study did not establish a major direct effect of job flexibility on strike participation, tests of interaction effects reveal that job flexibility moderates other mobilizing factors, such as union membership and job dissatisfaction. Job instability, on average, has no effect on strike participation.